THE CORRELATION BETWEEN ACADEMIC CHARACTERISTICS AND INTERACTION WITH THE QUR'AN ON MENTAL HEALTH - Al Faritzi, Muhamad Redho; Syari'ati, Zahra Mulki (IAIN Bone, 2025)
Mental health disorders are something that cannot be underestimated. In 2019, about 970 million people worldwide were living with a mental disorder equivalent to 1 in 8 people. The Qur'an can be the main therapeutic means with 5T aspects, namely recitation, tahfidz, tafsir, tathbig, and tabligh will get peace of mind that has an impact on mental health. This study is a quantitative correlation study to determine the relationship between the interaction of the Qur'an with mental health. This research was carried out at the Tasikmalaya Ministry of Health Polytechnic in November 2024 with a sample of the academic community who filled out a questionnaire from November 27 to December 4, 2024, which was taken using the purposive sampling method of 171 respondents. The instruments used were the Self-Reporting Questionnaire (SRQ) and questionnaires about interactions with the Qur'an to be further analyzed by gamma correlation tests. The result of this research shows the most mentally healthy in the group with good interaction with the Qur'an is 86.36% and mental disorders are detected in the group with less interaction with the Qur'an as much as 100%. The table shows the influence of interaction with the Qur'an on mental health with a p-value of 0.000. This research shows that interaction with the Qur'an will make you mentally healthy, in other words, the Qur'an is a means of mental health education